Peningkatan Pemahaman Siswa Kelas IV SD Tentang Wujud Zat Dan Perubahannya Melalui Game Edukasi Ular Tangga - Anissa Putri Ramadhania; Muhammad Suwignyo Prayogo; Ulfatul Rofida Alfikriyah (Universitas Palan, 2025)
The purpose of this study was to improve the understanding of fourth grade students of SDN Kaliwates 2 Jember about the form of substances and their changes by using snakes and ladders educational game. The background of this research is the lack of interest, motivation, and learning outcomes of students on abstract science materials. The teaching model used integrates the snakes and ladders game with the question mechanics of the lesson, where students who land on a box labeled